A Comprehensive Model for Whole Cell Sensing and Transmembrane Potential Measurement Using FET Biosensors. (7th February 2018) - Pulikkathodi, Anil Kumar; Sarangadharan, Indu; Chen, Yi-Hong; Lee, Geng-Yen; Chyi, Jen-Inn; Lee, Gwo-Bin; Wang, Yu-Lin
Abstract : In this research, the development of a highly sensitive FET based biosensor technology for whole cell sensing and cellular transmembrane potential measurement is discussed and a quantitative model is proposed to elucidate the sensor mechanism. Electrical double layer (EDL) gated FET biosensor platform offers high sensitivity target analyte detection, even in high ionic strength solutions, thereby eliminating the need for complex sample pre-processing methods. Using this sensor platform, we have developed a whole cell sensing technology that can detect and count cells, and monitor cellular bioelectric signals such as transmembrane potential changes. A quantitative model is developed to explain the sensor mechanism and theoretical prediction shows good agreement with experimental results. The changes in the cellular transmembrane potential upon extracellular stimulus is modeled based on the EDL FET sensor response. Our investigation reveals that EDL FET biosensor platform can be used to study the bioelectric signals of cells, dynamically which is highly relevant to cell biology in applications of drug development, ion channel studies and disease model establishment. This sensor technology can also be used for point of care diagnostics, in the diagnosis and prognosis of diseases such as cancer.